HALAL DAN HARAMNYA INVESTASI SAHAM BERBASIS SYARIAH DI PASAR MODAL - Qodir, Abdul; Kurniawan, Puji (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of investing can be used to improve people's welfare, guarantee finances in old age and even more broadly to improve the state of the country's economy to achieve economic stability. In general, people still think that investing in stocks is difficult and difficult and requires large funds, conditions like this are due to a lack of knowledge and socialization about investing in Islamic stocks. This study aims to find out about the law of investing in Islamic stocks, from the halal and haram sides. research method used in the form of literature study. Library research in the face of various literature in accordance with the objectives and problems that will be and are being studied. The conclusion from this study is that the law of buying and selling stocks and stock exchanges in Islam as long as the transaction method is carried out according to sharia demands and the types of shares purchased from companies that carry out their business in a halal manner, then all transactions in the capital market including shares are halal.